Laryngeal neurofibroma: case report and review of the literature - Gao, Yaya; Mo, Wei; Zhu, Hanwen; Zhang, Yunhan; Yang, Hui (Frontiers in Oncology, 2026)
BackgroundLaryngeal neurofibromatosis (LNF) represents an exceedingly rare manifestation of neurofibromatosis type 1 (NF1), a genetic disorder affecting neural tissue development with an incidence of approximately 1:3000 live births. While NF1 typically presents with cutaneous neurofibromas, laryngeal involvement is exceptional.MethodsA case of LNF associated with NF1 diagnosed at West China Hospital is presented, accompanied by a comprehensive literature review. A 21-year-old female presented with progressive hoarseness over two years. Diagnostic evaluation included physical examination revealing café-au-lait macules and laryngeal submucosal swelling, and computed tomography (CT) identifying a hypodense parapharyngeal space nodule. The patient underwent microlaryngoscopic excision of the mass. Histopathological examination and genetic analysis were performed.ResultsHistopathology confirmed the mass as a neurofibroma. Genetic analysis identified a pathogenic NF1 gene mutation. Microlaryngoscopic excision was successful, achieving complete removal with minimal intraoperative bleeding and no vocal cord damage, resulting in a favorable postoperative outcome.ConclusionsThis case details the successful diagnosis and management of rare laryngeal neurofibromatosis, confirming microlaryngoscopic excision as an effective approach. The integrated literature review synthesizes current understanding of this rare entity.